Wisata Perdesaan Berbasis Kebudayaan Masyarakat Desa Lamajang - Utami, Nisa Rahmaniyah; Rahadian, Wildan Rizky (Stupa, 2023)
This research aims to determine the shape & model of Lamajang village tourist. Rural tourism is a form of tourism in rural areas there are village community traditions, historical relics, art, and people's lifestyles along with the values that have been inherited passed down from generation to generation. The main attraction of the village Lamajang Village's tourism is a cultural and tourist attraction community activities. Rural tourism is a type of tourism that utilizes local resources in the form of culture and community activities. This research uses descriptive research methods with a qualitative approach. Lamajang Village has several potentials that can also be developed as an attraction, namely natural tourism in the form of a waterfall (waterfalls) and hiking trails that can be used as special routes an interesting tourist route through natural exploration activities. Rural tourism in Lamajang Village is a form of pure rural tourism with characteristics of semi-full models. In terms of product characteristics, Rural tourism in Lamajang Village still has shortcomings, namely: inadequate provision of facilities to support rural tourism activities in the form of homestays and rural tourism information centers.